Construcción de un vehículo tubular para las personas parapléjicas que pertenecen y estén relacionadas con el consejo nacional de igualdad y discapacidad (conadis) del cantón El Empalme, zona de influencia de la ciudad de Quevedo, año 2015 - Briones Vera, Joffre Daniel (2015)
The present project has a proposal for the construction of a vehicle for people with stroke problem through the CONADIS for its effect. The intervention of different factors such as technology has influence the modern age with improvements through the development of such projects that are linked together with the research and analysis of the results The necessary studies were realized to determine the number of people with limited mobility, where this process of construction is defined, the model and type of vehicle in which will be used in the canton of "El Empalme" and all vulnerable sector of the Guayas province. The overall objective for this research is to be able to carry out the structuring of this vehicle for people with this type of disability, so that they can be mobilized without difficulties The research also will rely on the use of the surveys where the aim is to obtain information provided directly from disabled people with partial stroke problems. As main recommendations the Ecuadorian State government should orientate people so that they may acquire this type of vehicle and on the other hand, a greater investment for its construction. The vehicle has a system with satisfying proposal for those who need them for everyday use, which is powered by different systems such as levers, hand brakes and offers a great ease of driving it. To carry out the analysis of the different parts and materials different calculations and simulation were held by different to verify that what’s been used is effective; specifications were determined at the time of construction that allows the user to drive it safely, complying with established quality conditions. The solution for people with stroke is defined from verifying economically the worth of this vehicle in the market to deference to this prototype that exceeds expectations by its low cost and performance on the road. Based on the results, we conclude that the vehicle built is beneficial, improving the quality of life and transport of people suffering from paralysis since it complies with the standards and norms.